Nanotechnology in Civil Infrastructure A Paradigm Shift - Gopalakrishnan, Kasthurirangan; Birgisson, Bjorn; Taylor, Peter; Attoh-Okine, Nii O.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Nanotechnology in Civil Infrastructure is a state-of-the art reference source describing the latest developments in nano-engineering and nano-modification of construction materials to improve the bulk properties, development of sustainable, intelligent, and smart concrete materials through the integration of nanotechnology based self-sensing and self-powered materials and cyber infrastructure technologies, review of nanotechnology applications in pavement engineering, development of novel, cost-effective, high-performance and long-lasting concrete products and processes through nanotechnology-based innovative processing of cement and cement paste, and advanced nanoscience modeling, visualization, and measurement systems for characterizing and testing civil infrastructure materials at the nano-scale. Researchers, practitioners, undergraduate and graduate students engaged in nanotechnology related research will find this book very useful. .
Multifunctional and Smart Carbon Nanotube Reinforced Cement-based Materials -- Applications of Nanotechnology in Road Pavement Engineering --   Application of Nanoscience Modeling to Understand the Atomic Structure of C-S-H --   The Effect of SWCNT and Other Nanomaterials on Cement Hydration and Reinforcement   --   Nanomaterials-enabled Multifunctional Concrete and Structures --   Nano-Optimized Construction Materials by Nano-Seeding and Crystallization Control --   Next-Generation Nano-based Concrete Construction Products: A Review --   Optimization of Clay Addition for the Enhancement of Pozzolanic Reaction in Nano-modified Cement Paste --   Characterization of Asphalt Materials for Moisture Damage Using Atomic Force Microscopy and Nanoindentation --   Nanoclay-modified Asphalt Binder Systems   Optimization of Clay Addition for the Enhancement of Pozzolanic Reaction in Nano-modified Cement Paste --   Characterization of Asphalt Materials for Moisture Damage Using Atomic Force Microscopy and Nanoindentation --   Nanoclay-modified Asphalt Binder Systems.
Keywords: Civil engineering; Nanotechnology; Sustainable development; Renewable energy resources; Computational intelligence; Regional planning; Urban planning; Civil Engineering; Nanotechnology; Sustainable Development; Renewable and Green Energy; Computational Intelligence; Landscape/Regional and Urban Planning